The accuracy of antenatal fetal echocardiography - Özkutlu, Süheyla; Saraçlar, Muhsin (The Turkish Journal of Pediatrics, 1999)
The purpose of this study was to evaluate our experience with a group of patients who were either selected by us or referred by an obstetrician or geneticist with the indication of fetal echocardiography.This prospective study was done on 128 cases between 1996-1998. Maternal age range was between 16 and 41 years (mean: 28.79). Gestational age range was between 15 and 37 weeks (mean: 26). In the postnatal period the newborn babies were reevaluated for cardiovascular system abnormalities by physical examination, ECG, telecardiogram and, if it was necessary, by echocardiography, cardiac catheterization and angiography. By comparing prenatal and postnatal findings, sensitivity and specificity of fetal echocardiographic diagnosis were determined. Among the total cases studied, nine had major congenital heart disease in postnatal evaluation. Two cases had false negative; there were no false positive prenatal diagnoses. Sensitivity of echocardiographic diagnosis was 100 percent and specificity 78 percent. Three patients had paroxysmal atrial tachycardia and two atrioventricular block. We concluded that the fetal echocardiography is a very useful technique in the evaluation of the fetal cardiovascular system. However, awkward fetal position, severe maternal obesity, and technologic insufficiency of the echo machine may result in unfavorable scanning conditions. Minuteness of anomaly may also result in a false negative prenatal evaluation.
Keywords: echocardiography; fetal echocardiography; fetus; congenital heart disease; dysrhythmia